The foundations of fracture impedance spectroscopy. (August 2019) - Macdonald, Digby D.; Fekete, Balazs
Abstract: The foundations of Fracture Impedance Spectroscopy (FIS) as a theoretical framework for analyzing and predicting fatigue and corrosion fatigue crack growth rate in real structures under complex loading waveforms from laboratory data obtained under simple, "pristine" loading conditions is presented. FIS is based upon an analogy between current flow (crack growth rate) in an electrical circuit in response to an applied, time-dependent voltage (time-dependent stress intensity factor). In this paper, the framework of the theory and its application for two different aerospace alloys are presented. Highlights: The theory of Fracture Impedance Spectroscopy (FIS) is presented. Crack growth rate (CGR) can be calculated using stress intensity factor (SIF) for arbitrary loading waveform and frequency. FIS is based upon an analogy between current flow (CGR) in an electrical circuit in response to a voltage (SIF). "Fracture impedance" for crack growth in metal defined by transforming the perturbation and response into the Laplace frequency domain. Crack growth rate calculations show the viability of the FIS concept.